Applications of Real Numbers (ℝ) in Economics and Financial Models (NUTA Journal, 2024)
This article explores the significance of real number theory in economics and finance, focusing on its role in improving the accuracy and reliability of economic analyses. As applied mathematics continues to evolve, real number theory has become an essential tool for economists and financial analysts. The main objective is to demonstrate how real numbers are used in various financial calculations, including interest rates, present value, inflation, GDP growth, risk management, and portfolio analysis.To achieve this, a comprehensive review of relevant mathematical and financial literature was conducted, accompanied by a theoretical analysis of the properties of real numbers and their applications in economic contexts. Key concepts such as the Completeness Property, Archimedean Property, and important theorems like the Bolzano-Weierstrass Theorem and the Mean Value Theorem were examined. Practical examples and case studies were provided to illustrate how these principles can address real-world economic and financial challenges.The findings highlight that real number theory is crucial in financial modeling and economic forecasting. It aids in optimizing production levels and assessing risks in investment portfolios. Overall, this article emphasizes the importance of integrating real number theory into economic research to enhance analysis and decision-making in the financial sector.